The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1365-2966.2011.19554.x
|View full text |Cite
|
Sign up to set email alerts
|

UBV(RI)C photometry of transiting planet hosting stars

Abstract: We present new UBV(RI)C photometry of 22 stars that host transiting planets, 19 of which were discovered by the Wide Angle Search for Planets (WASP) survey. We use these data together with Two Micron All Sky Survey (2MASS) JHKS photometry to estimate the effective temperature of these stars using the infrared flux method. We find that the effective temperature estimates for stars discovered by the WASP survey based on the analysis of spectra are reliable to better than their quoted uncertainties.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 47 publications
(30 reference statements)
3
22
0
Order By: Relevance
“…The T eff values obtained from CORALIE spectra have been found to be in agreement with those from the infrared flux method (Maxted et al 2011), suggesting that a change of more than 100 K is unlikely. However, Doyle et al (2012) found that [Fe/H] obtained using CORALIE spectra is, on average, 0.08 ± 0.06 dex lower than found using higher S/N HARPS spectra.…”
Section: Discussionsupporting
confidence: 67%
“…The T eff values obtained from CORALIE spectra have been found to be in agreement with those from the infrared flux method (Maxted et al 2011), suggesting that a change of more than 100 K is unlikely. However, Doyle et al (2012) found that [Fe/H] obtained using CORALIE spectra is, on average, 0.08 ± 0.06 dex lower than found using higher S/N HARPS spectra.…”
Section: Discussionsupporting
confidence: 67%
“…In the case of SWP, we do not deeply check whether the different sources give photometry de-reddened or not because neither SWEET-Cat nor the Exoplanets Data Explorer report any reddening information. We explicitely account for reddening in the case of those TPH listed in Maxted et al (2011), who report the colour excess E(B − V). Anyway, by a posteriori catalogue cross-matching, we were able to recover E(B − V) index for 154 stars out of the 335 SWP, and we found that more than 80% of them has E(B − V) = 0.…”
Section: Isochrone Placement: Implementationmentioning
confidence: 99%
“…The metallicity [Fe/H] and the logarithm of the surface gravity log g are always available from Sweet-Cat. If available, we took V magnitude and B − V colour index from Maxted et al (2011), otherwise we collected V from SWEET-Cat and B − V from The Site of California and Carnegie Program for Extrasolar Planet Search: Exoplanets Data Explorer 2 . As reported by Maxted et al (2011), the target stars of surveys that aim to discover exoplanets through transits are typically characterized by optical photometry of poor quality in the range V = 8.5−13 mag.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The host star WASP-2A is an R = 11.3 spectral type K1 dwarf, with an effective temperature of T eff = 5110 ± 60 inferred from optical and infrared colors (Maxted et al 2011), T eff = 5150 ± 80 K using photospheric fitting of spectroscopic data (Triaud et al 2010), and metallicity of [Fe/H] = 0.08 ± 0.08 (Triaud et al 2010). In our modeling we included photometric data from previous publications including Southworth et al (2010), who converted the timings from Cameron et al (2007), Charbonneau et al (2007), and Hrudková et al (2009) into the common time standard BJD(TDB) as outlined by Eastman et al (2010), as well as one transit epoch from Sada et al (2012).…”
Section: Apostle Programmentioning
confidence: 99%